Network externalities and spillovers in the email client software. - Yingyot Chiaravutthi. (2014)
This paper analyzes adoption decisions of email client software with the focus on network externalities, spillovers, and firms’ strategies. Survey data are used to test the existence of network externalities and spillovers by studying the claimed reasons for adoption. Based on the GVU WWW User Survey data in 1997 and 1998, logit models are employed to test hypotheses. The results show that Eudora’s competitive advantages were derived from its high quality product which was perceived by users, loyalty which was created from users’ prior experience, and network externalities and spillovers which were driven by high market share. Sources of network externalities and spillovers are outside accessibility and others’ recommendations, respectively. These advantages diminished when Netscape employed bundling with its suite, and when Microsoft employed bundling with its operating system and free strategies.